2015
DOI: 10.3389/fpubh.2015.00005
|View full text |Cite
|
Sign up to set email alerts
|

Consequence of Indoor Air Pollution in Rural Area of Nepal: A Simplified Measurement Approach

Abstract: People of developing countries especially from rural area are commonly exposed to high levels of household pollution for 3–7 h daily using biomass in their kitchen. Such biomass produces harmful smoke and makes indoor air pollution (IAP). Community-based cross-sectional study was performed to identify effects of IAP by simplified measurement approach in Sunsari District of Nepal. Representative samples of 157 housewives from household, involving more than 5 years in kitchen were included by cluster sampling. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 24 publications
2
46
0
Order By: Relevance
“…Mothers and children were mostly those under this heavy load of HAP. Because of their customary involvement in cooking, especially women's exposure is much higher than men's (3,12,(14)(15)(16) with children either been carried on the back during cooking hours or laid to sleep on kitchen beds during the cooking process.…”
Section: Factors Influencing the Choice Of Fuel Typementioning
confidence: 99%
“…Mothers and children were mostly those under this heavy load of HAP. Because of their customary involvement in cooking, especially women's exposure is much higher than men's (3,12,(14)(15)(16) with children either been carried on the back during cooking hours or laid to sleep on kitchen beds during the cooking process.…”
Section: Factors Influencing the Choice Of Fuel Typementioning
confidence: 99%
“…Respiratory disease is one of the leading causes of death in Nepal, causing more deaths annually than the diseases used as SD indicators in MDG 6 (tuberculosis, malaria and HIV/AIDS) [79,80]. Women and children generally spend more time than men near cook stoves, and the pollution disproportionately impacts women and young children [71,79]. Furthermore, firewood (and water) collection in many areas takes up a considerable amount of time, leaving limited time for women and girls for education and income-generating activities [81,82].…”
Section: Co 2 Emissions and Energy Consumptionmentioning
confidence: 99%
“…A number of studies in Nepal have shown a strong correlation between particulate matter from traditional cook stoves and diseases like acute lower respiratory infection, chronic bronchitis, and chronic obstructive pulmonary disorder [78,79]. Respiratory disease is one of the leading causes of death in Nepal, causing more deaths annually than the diseases used as SD indicators in MDG 6 (tuberculosis, malaria and HIV/AIDS) [79,80].…”
Section: Co 2 Emissions and Energy Consumptionmentioning
confidence: 99%
“…In a cross-sectional study of 841 rural Mexican women, use of biomass fuel was associated with increased risks of respiratory symptoms and higher kitchen particulate matter concentration, compared with gas fuel use [14]. In a community-based cross-sectional study involving 157 Nepalese housewives, the most frequently reported health problem related to household air pollution was tearing eyes, followed by breathlessness and productive coughing [15]. By comparing household air pollution concentration in 824 households in rural Nepal, average particulate matter less than 2.5 µm in diameter (PM 2.5 ) concentrations were lower in households using kerosene (169 µg/m 3 ), gas (101 µg/m 3 ), and electricity (80 µg/m 3 ), compared to households using solid fuels (656 µg/m 3 ) [16].…”
Section: Introductionmentioning
confidence: 98%